Concept of integration of blockchain and artificial intelligence - Alwi, Shaliza; Mohd Salleh, Masrina Nadia; Abu Yaziz @ Mohamad, Mohd Fathi; Ismail, Albert Feisal; Abbas, Mohd Saleh; Haris Fadzilah, Asmaul Husna (IEEE, 2023)
Blockchain is a secure, decentralised way to move and store data. Whereas AI is a process which makes use of learning through self and is founded on the examination and identification of patterns in vast volumes of data. It also evaluates and makes judgments based on the study of a lot of data using supervised or unsupervised learning. The foundation of this essay is a conceptual understanding of how blockchain and AI could complement one another or how blockchain might help AI. It indicates that both can eventually be combined for the advantage of both businesses and the people dealing with it.